2023
DOI: 10.1177/17562848231210367
|View full text |Cite
|
Sign up to set email alerts
|

Geographical heterogeneity in the disease characteristics and management of patients with inflammatory bowel disease, the preliminary results of a Chinese database for IBD (CHASE-IBD)

Jian Wan,
Jun Shen,
Xiaoping Wu
et al.

Abstract: Background: The incidence of inflammatory bowel disease (IBD) is rapidly increasing in China, a vast country with significant geographical differences. The socioeconomic status of Eastern China is significantly higher than that of Western China. Objectives: This study aimed to describe the geographical heterogeneity in the characteristics and management of patients with IBD in both Eastern and Western China. Design: This was a multicenter, cross-sectional study. Methods: Patients with IBD with ages ⩾18 years u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In CD patients, sex had an influence on the likelihood of hospitalization, with a higher likelihood among men, but not on surgery, whereas in UC patients, sex was associated with surgery, with a higher likelihood among men, but it was not associated with hospitalization. Although sex-based differences were found, many studies reported no statistically significant sex differences in either the likelihood of surgery or hospitalization [ 26 , 34 , 36 38 , 41 43 , 45 , 46 , 48 , 49 , 51 , 54 , 57 , 59 – 61 , 65 , 68 , 71 , 76 80 , 84 ]. Similar results were observed in a review by Rustgi et al, that reported males generally undergo more IBD-related surgery than females [ 12 ], yet another study from the review by Rustgi et al revealed higher probabilities among female patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In CD patients, sex had an influence on the likelihood of hospitalization, with a higher likelihood among men, but not on surgery, whereas in UC patients, sex was associated with surgery, with a higher likelihood among men, but it was not associated with hospitalization. Although sex-based differences were found, many studies reported no statistically significant sex differences in either the likelihood of surgery or hospitalization [ 26 , 34 , 36 38 , 41 43 , 45 , 46 , 48 , 49 , 51 , 54 , 57 , 59 – 61 , 65 , 68 , 71 , 76 80 , 84 ]. Similar results were observed in a review by Rustgi et al, that reported males generally undergo more IBD-related surgery than females [ 12 ], yet another study from the review by Rustgi et al revealed higher probabilities among female patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%